1995
DOI: 10.1002/pros.2990270504
|View full text |Cite
|
Sign up to set email alerts
|

Work environment and prostate cancer risk

Abstract: ABSTRACT:A cas e-referent study of 345 prostate cancer cases and 1,346 referents was carried out in the Netherlands to investigate the relationship between work environment and prostate cancer risk. Cases were selected from the Cancer Registry of the Comprehen sive Cancer Centre IKO. Referents (men diagnosed with benign prostate hyperplasia) were recruited with assistance of the pathology laboratories in the IKO region. Questionnaires were mailed to all subjects to obtain information on their work history and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 31 publications
2
81
2
1
Order By: Relevance
“…A large casecontrol study found that most of the jobs associated with prostate cancer had the potential for occupational PAH exposure [12]. In three separate studies that examined specific occupational exposures, two found modest associations between selected PAH sources and prostate cancer [14,15], while the third found no link between PAH-related exposures and prostate cancer [42]. It is important to note that the two studies that found some associations between PAH exposures and prostate cancer used the expert review method utilized in the present study, whereas the negative study only used self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…A large casecontrol study found that most of the jobs associated with prostate cancer had the potential for occupational PAH exposure [12]. In three separate studies that examined specific occupational exposures, two found modest associations between selected PAH sources and prostate cancer [14,15], while the third found no link between PAH-related exposures and prostate cancer [42]. It is important to note that the two studies that found some associations between PAH exposures and prostate cancer used the expert review method utilized in the present study, whereas the negative study only used self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Both case-control (12) and cohort (13) studies have found that most jobs associated with prostate cancer have the potential for occupational PAH exposure. In three separate studies that examined specific occupational exposures, two found modest associations with selected PAH sources (14,15), whereas the third found no association with PAH-related exposures (16). PAH exposures that occur years before disease onset may have a greater impact on prostate carcinogenesis.…”
Section: Introductionmentioning
confidence: 93%
“…The high temperature associated with mold and core making and casting processes often results in the emission of several pyrolysisinduced PAH, including benzo[a]-pyrene. In three separate studies that examined specific occupational exposures, two found modest associations with selected PAH sources [15,16], while the third found no association with PAH-related exposures [17]. Three case-control studies have found an elevated prostate cancer risk for exposure to diesel fumes [16,18,19].…”
Section: Epidemiologic Studies Of Pah Exposures and Prostate Cancermentioning
confidence: 99%